Role Of Stress Amongst Nurses At The Workplace: Concept Analysis - Alharbi, Yousef Owaidh Alhurayr; alsehli, Turki Hamed Thawap; Alsahli, Fawaz Hammad Bakhet; Alsahli, Jaser Hamadi Mohammed; Alharbi, Abdulah Ayed Jabr; Alsehli, Mohammed Hamed Bakhet; Alsehli, Salman Helal Salem; Alsahli, Nasser Ali Dakhil (Migration Letters, 2022)
The aim of this paper was to review the literature on factors related to role stress in nurses, and present strategies for addressing this issue based on the findings of this review while considering potential areas for development and research. Computerized databases were searched as well as hand searching of articles in order to conduct this review. This review identified multiple factors related to the experience of role stress in nurses. Role stress, in particular, work overload, has been reported as one of the main reasons for nurses leaving the workforce. This paper conclu[1]des that it is a priority to find new and innovative ways of supporting nurses in their experience of role stress. Some examples discussed in this article include use of stress education and management strategies; team-building strategies; balancing priorities; enhancing social and peer support; flexibility in work hours; protocols to deal with violence; and retention and attraction of nursing staff strategies. These strategies need to be empirically evaluated for their efficacy in reducing role stress.